Notifiche
Cancella tutti

Qualcuno sa farlo?

  

0
IMG 7370
Autore
2 Risposte



0

Credo di si 

IMG20250204165953



0

$ \int \frac{2x}{(x-1)^3} \, dx = $

$ = 2 \int \frac{x}{(x-1)^3} \, dx = $

per sostituzione. Poniamo $ t = x-1 \; ⇒ \; x = t+1 \; ⇒ \; dx = dt$

$ = 2 \int \frac{t+1}{t^3} \, dt = $

$ = 2 \int \frac{t}{t^3} \, dt + 2 \int \frac{1}{t^3} \, dt = $

$ = 2 \int t^{-2} \, dt + 2 \int t^{-3} \, dt = $

$ = -\frac{2}{t} -\frac{2}{t^2} + c$

$ = -\frac{2}{x-1} -\frac{2}{(x-1)^2} + c$



Risposta
SOS Matematica

4.6
SCARICA